PENGARUH KINERJA KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS - Bader, Muchamad Abu; Damayanti, Cacik Rut (Program Studi Akuntansi, Universitas Kuningan, 2024)
The purpose of this research is to examine and analyze the effect of financial performance and corporate governance on financial distress. Projected financial performance as a proxy for Current Ratio (CR), Debt Ratio (DR), Return On Assets (ROA) and corporate governance projected as a proxy for Independent Commissioners while financial distress is measured using the modified Altman Z- Score method for state-owned companies listed on the Stock Exchange Indonesiansecurities for the period 2018-2021. The number of samples used was 10 samples from 22 populations of BUMN companies listed on the Indonesia Stock Exchange which were selected using a purposive sampling method. Data processing method used multiple linear regression analysis. The partial results of the study show that current ratio has a significant effect on financial distress, debt ratio has a significant effect on financial distress. While, return on assets has no significant effect on financial distress and independent commissioners have significant effect on financial distress. Simultaneous test results: current ratio, debt ratio, return onassets and Independent commissioners have a significant effect on financial distress in state-owned companies listed on the IDX for the 2018- 2021 periodKeywords: Financial Performance, Corporate Governance, Financial distress